Anti-β2-glycoprotein I paratopes and β2-glycoprotein I epitopes characterization using random peptide libraries. (November 2014) - Žager, Urška; Kveder, Tanja; Čučnik, Saša; Božič, Borut; Lunder, Mojca
Abstract Studies concerning interactions between anti-β2-glycoprotein I antibodies (anti-β2GPI) and β2-glycoprotein I (β2GPI) suggest relevance of charge interactions and hydrogen bonds. However, paratope of diagnostically and clinically relevant anti-β2GPI and epitope characteristics of β2GPI, still remain unclear. The aim of our study was to determine paratope characteristics of various anti-β2GPI antibodies and epitope characteristics of β2GPI using phage display. Monoclonal IgG anti-β2GPI, purified polyclonal high avidity and low avidity IgG anti-β2GPI derived from plasma of APS patients were used to screen phage display libraries. The affinity and competition ability of selected clones were evaluated. Various heptapeptides presenting putative paratopes of anti-β2GPI and specific heptapeptides presenting putative epitopes of β2GPI were determined. Epitope presenting peptides bind to the respective anti-β2GPI and consequently interrupt antibody–antigen interaction. The amino acid composition of selected peptides confirmed the importance of hydrogen bonds and charge interactions in the binding of anti-β2GPI to the antigen. Epitopes recognized by high avidity anti-β2GPI predominately contain hydrogen bond forming side chains, while in low avidity anti-β2GPI epitope the charged side chains prevail. The alignment of selected sequences to three-dimensional antigen structure revealed that polyclonal high avidity anti-β2GPI recognize native epitopes that are accessible regardless of β2GPI's conformation whereas the epitope recognized by low avidity anti-β2GPI is cryptic and cannot be accessed when β2GPI takes the closed plasma conformation.